Evidence for two cell division cycle (CDC) genes that govern yeast bud emergence in the pathogenic fungus Wangiella dermatitidis. - Cooper, C R (1993)
Strains Mc2 and Mc3 are morphological mutants of the melanized, pathogenic fungus Wangiella dermatitidis. These strains possess temperature-sensitive (ts) mutations designated mcm2 and mcm3, respectively. At the restrictive temperature (37 degrees C), uninucleate yeast cells of strains Mc2 and Mc3 cease budding and initiate an isotropic mode of cellular development, which is reflected in the formation of a multicellular and multinucleate morphology. Because W. dermatitidis either lacks or has an undiscovered sexual cycle, parasexual methods of analysis were used to confirm that mcm2 and mcm3 define separate bud emergence control genes in the wild-type strain. Spheroplasts of albino auxotrophs derived from strains Mc2 and Mc3 were fused and then regenerated on minimal medium. The resulting fusion products grew as darkly pigmented, prototrophic colonies. When incubated at 37 degrees C, all fusion products exhibited polarized growth predominantly as uninucleate, budding yeasts and less frequently as pseudohyphae and moniliform hyphae. Subsequent analysis of cultures derived from albino, ts segregants, which were induced from fusion products by using methyl benzimidazole-2-yl-carbamate, revealed three types of cell populations. Two resembled those expressed by strain Mc2 or Mc3. The third consisted of a cell population unlike the former, suggesting the presence of both ts mutations in all cells. These results imply that yeast development in the fusion products resulted from intergenic complementation of mcm2 and mcm3, i.e., they are nonallelic. Because mcm2 and mcm3 are equivalent to certain cdc lesions in the yeast Saccharomyces cerevisiae, we have renamed the analogous genes defined by the mutations in W. dermatitidis as CDC1 and CDC2. To our knowledge, these are the first CDC genes identified in a dematiaceous fungus.